2004
DOI: 10.3136/fstr.10.56
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Triterpenes and Sterol from the Fruit of Rabbiteye Blueberry (Vaccinium ashei)

Abstract: Seven triterpenes, ␣-amyrin (1), uvaol (2), ursolic acid (3), ␤-amyrin (4), erythrodiol (5), lupeol (6) and betulin (7), two sterols, ␤-sitosterol (8) and ␤-sitosterol 3-O-␤-glucopyranoside (9), and one flavonoid, syringetin 3-O-␣-rhamnopyranoside (10) were isolated from the methanol extract of the fruit of rabbiteye blueberry (Vaccinium ashei). Their chemical structures were determined on the basis of spectroscopic data. Among them, 3, 4 and 9 exhibited moderate growth inhibitory activity against human lung c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 17 publications
0
20
0
1
Order By: Relevance
“…In vitro studies into 83's effects indicated that it acted by inducing apoptosis (Fernandes et al, 2003;Huang et al, 2003b;Urech et al, 2005), but it also had other effects: it inhibited the invasive, adhesive, and migration abilities of lung cancer cells (Huang et al, 2003b); showed antiangiogenic activity, possibly by inhibiting proliferation of vascular endothelial cells (Sohn et al, 1995); and induced differentiation, which does not proceed normally in some cancer types (Umehara et al, 1992). 3-Acetoxy-oleanolic acid (84), β-amyrin (88), and katononic acid (90) also showed varying degrees of cytotoxicity to cancer cells (Kaneda et al, 1992;Topcu et al, 2003;Ono et al, 2004), and 84 had some differentiation-inducing activity (Umehara et al, 1992).…”
Section: Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies into 83's effects indicated that it acted by inducing apoptosis (Fernandes et al, 2003;Huang et al, 2003b;Urech et al, 2005), but it also had other effects: it inhibited the invasive, adhesive, and migration abilities of lung cancer cells (Huang et al, 2003b); showed antiangiogenic activity, possibly by inhibiting proliferation of vascular endothelial cells (Sohn et al, 1995); and induced differentiation, which does not proceed normally in some cancer types (Umehara et al, 1992). 3-Acetoxy-oleanolic acid (84), β-amyrin (88), and katononic acid (90) also showed varying degrees of cytotoxicity to cancer cells (Kaneda et al, 1992;Topcu et al, 2003;Ono et al, 2004), and 84 had some differentiation-inducing activity (Umehara et al, 1992).…”
Section: Cancermentioning
confidence: 99%
“…Though its inhibitory activity against cancer cell lines was moderate at best (Ratnayake et al, 1992;Chang et al, 2003;Ono et al, 2004), it showed antileukemic effects in mice (Nozaki et al, 1986).…”
Section: Insecticidal Activity: α-Amyrin (99) Caused Molting In Spodomentioning
confidence: 99%
“…The genus produce a wide range of compounds including anthocyanins [3,, flavonoids [20-23, 28, 37, 40, 42, 46-75], coumarins [73], lignans [76], benzoic acids [77][78][79][80], iridoids [81][82][83], sterols *Address correspondence to this author at the National Center for Pharmaceutical Crops, Arthur Temple College of Forestry and Agriculture, Stephen F. Austin State University, Nacogdoches, TX 75962, USA; Tel: 936-468-5646, 936-468-5600; Fax: 936-468-7058; E-mail: suz@sfasu.edu [84][85][86][87], triterpenoids [52,55,84,88,89], but are best known for the production of bioactive anthocyanins and flavonoids. To date, more than 116 anthocyanins and flavonoids compounds have been isolated and identified primarily from the fruits and leaves of Vaccinium.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds 3-16 were identified as gelsemiol 3-O-b-Dglucoside (3), 3) verbraside (4), 2) 9-hydroxysemperoside (5), 3) griselinoside (6), 4) aralidioside (7), 4) 6) acteoside (10), 7) leucosceptoside A (11), 8) (15), 12) and b-sitosterol (16), 12) respectively, based on their physical and spectral data, although detailed 1 H-NMR spectral data and 13 C-NMR spectral data in CD 3 OD of 3-8 have not been reported in the literature. The structures of compounds 1-8 are shown in Fig.…”
mentioning
confidence: 99%
“…The aqueous MeOH layer was successively subjected to Diaion HP20 and silica gel column chromatography as well as HPLC on ODS to afford 15 compounds (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Chromatography of the hexane layer over silica gel and Diaion HP20 furnished 16.…”
mentioning
confidence: 99%